5th Independent Science Panel Meeting, Rome, Italy, 10-11 October 2013 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In October 2013 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its fifth Independent Science Panel meeting in Rome, Italy.